Symmetric equilibria in stochastic timing games - Jan-Henrik Steg (Bielefeld University, Center for Mathematical Economics (IMW), 2015)
We construct subgame-perfect equilibria with mixed strategies for symmetric stochastic timing games with arbitrary strategic incentives. The strategies are qualitatively different for local first- or second-mover advantages, which we analyse in turn. When there is a local second-mover advantage, the players may conduct a war of attrition with stopping rates that we characterize in terms of the Snell envelope from the general theory of optimal stopping, which is very general but provides a clear interpretation. With a local first-mover advantage, stopping typically results from preemption and is abrupt. Equilibria may differ in the degree of preemption, precisely at which points it is triggered. We provide an algorithm to characterize where preemption is inevitable and to establish the existence of corresponding payoff-maximal symmetric equilibria.
urn:nbn:de:0070-pub-27638304
Keywords: C61; C73; D21; L12; 330; Stochastic timing games; mixed strategies; subgame perfect equilibrium; Snell envelope; optimal stopping